Stock return synchronicity in a weak information environment: Evidence from African markets - Kyiu, A.; Jones, E.; Li, H. (International Journal of Managerial Finance, 2025)
Purpose: This study investigates the level of stock return synchronicity in African markets with the aim of establishing whether, contrary to conventional wisdom, stock return synchronicity can be low in countries with relatively weak information environments. Design/methodology/approach: The authors use a sample of five African countries (Botswana, Ghana, Kenya, Nigeria and South Africa) and a total of 616 firms over the period 2005–2015. This study's main measure of synchronicity is the R2 from a regression of stock returns on index returns. The authors also carry out regression analysis to investigate the main firm-level drivers of synchronicity. Findings: On average, firms in African markets do not exhibit high levels of stock return synchronicity, providing support for the view that stock return synchronicity can be low in markets with relatively weak transparency. The authors, however, observe an increase in the level of synchronicity during the global financial crisis, notably for Ghana and Kenya. In the regression analysis, the main firm-level driver of synchronicity is firm size, while contrary to some previous studies, ownership structure has no impact. The authors also find evidence of the impact of changes in accounting regulation, notably the mandatory adoption of IFRS, on the level stock synchronicity. Originality/value: This study contributes to the understanding of stock return synchronicity and how price discovery can vary between different information environments. The authors argue that stock returns in African countries may not always fit the stereotypical view that they are synchronous. The level of synchronicity among firms suggests that corporate events may carry some stock price implications.
EPrint Processing Status: Full text deposited in DRO